The Anglo-Catholic Perspective of George Gascoigne’s 1572 Masque of Montacutes - Stelzer, Emanuel (Early Theatre, 2024)
When considering Gascoigne’s 1572 masque, scholars often point out the poet’s ingenuity in connecting the surname of his patron with the Montagues and Capulets of the Romeo and Juliet story and in interweaving that fictional feud with two historical events which had recently taken place in the Mediterranean: the siege of Famagusta and the Battle of Lepanto. Building on this work, this essay revisits the sociopolitical premises of Gascoigne’s text, emphasizing their transnational character and considering how the triangulation of Englishness, Catholicism, and the dehumanization of the Turks fit into the Elizabethan cultural context.